Penerapan Digital Content #CiptakanKebaikan sebagai Bentuk Promosi pada Platform Tiktok - Ihda 'Ainaya Zulaikha; Khusnul Khotimah (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Tiktok is a social media that now has the potential to promote products ranging from goods, services, or information that can be delivered quickly. The context of communication teaches several important roles including about 'messages', how good message content will bring up a person's responsive attitude, so that messages in the realm of promotion on the Tiktok platform are to show content ideas in visual form. Problems or social phenomena regarding visual violence or cyberbullying are a form of shared unrest, so the Ministry of Information and Communication (KOMINFO) collaborates with Tiktok to promote a #CiptakanKebaikan campaign to provide understanding and create digital forms of conversation in the current era. This study uses a qualitative method where researchers see how this campaign is formed so as to form a Digital Literacy. The researcher uses the Critical Discourse Analysis approach as an accurate form to reflect on how the analysis is built in the campaign. The researcher analyzed the entire content regarding #CiptakanKebaikan to see how the implementation of this campaign could be utilized by Tiktok social media and the implications of that content for building Digital Literacy. The results of the research show that there are three content used in the #CiptakanKebaikan campaign including storytelling, sharing, and experience.